Dinamika Keterwakilan Perempuan dalam Politik - Citra Dewi Agustin; Dyah Ayu Nurhayati Asih (Universitas Islam Balitar, 2025)
Women's political representation in the world today has made significant progress, although it still faces many obstacles. Although many countries, including Rwanda and the Nordic countries, have successfully increased women's representation through quota policies, women still face major challenges in the form of discrimination, gender-based violence, and social stereotypes. The reality in Indonesia is still distant from this goal, even though the country has an affirmation policy that mandates a minimum quota of 30% of women`s representation. This study is to investigate the roles and difficulties faced by women in politics, the effects of affirmative action laws, and the necessary steps to enhance women's involvement in political decision-making. The research method used is qualitative, using an approach that emphasizes literature study. The results show that despite the increase in women's representation in parliament, structural barriers and patriarchal culture are still the main challenges. Therefore, sustainable efforts are needed in the form of political education, structural support from political parties, and revision of regulations to strengthen affirmation policies to realize more equal political representation of women.